Rethinking Institutional Frameworks in Conservation and Governance of Forests in the Background of FRA in Kerala: From Exclusion to Inclusion - K H Amitha Bachan and Maya M (Artha-Journal of Social Sciences, 2017)
The forward and backward linkages between conservation, governance and people‟s initiatives have been a widely accepted paradigm in the domain of sustainable forest management. Forest Rights Act, 2006, is remarkable as it is the only law which is based on the principles of inclusion by recognizing the decision making authority of hamlet level Gram Sabhas in conservation. This paper looks at the existing institutional frameworks for conservation, i.e. forest and its resource management including land tenureship and to address societal needs of ethnic communities. The analysis is done within the backdrop of the assigned roles of hamlet level Gram Sabhas in FRA with special focus on the Anamalai region, Central Kerala within the distribution area of Kadar (notified particularly vulnerable) ethnic community. The progress of FRA implementation in this region has been discussed as a measure of the shifting of exclusive institutional frameworks to an inclusive one.